Secretion of fowl plague virus haemagglutinin from insect cells requires elimination of both hydrophobic domains - Kretzschmar, Evelyne; Veit, Michael; Brunschön, Sabine; Kuroda, Kazumichi; Klenk, Hans-Dieter (Journal of General Virology, 1992)
In the present study we have investigated the role of the hydrophobic domains of the fowl plague virus (FPV) haemagglutinin (HA) on its intracellular transport and maturation in insect cells. To this end processing of full-length HA (A+) has been compared to that of two truncated forms lacking either the cytoplasmic domain and the transmembrane domain (A−) or lacking the entire HA2 subunit, i.e. the transmembrane domain and the fusion peptide (HA- 2). All glycosylation sites present on A− and HA- 2 were glycosylated, indicating that both truncated forms were completely translocated in the endoplasmic reticulum. Unlike A+, A− and HA- 2 did not form trimers as indicated by cross-linking, gradient centrifugation and studies employing conformation-specific antibodies. Whereas HA- 2 was efficiently secreted, A− was retained in the cells in an apparently membrane-bound form. The data show that the carboxy-terminal transmembrane region is essential for the formation and stability of the trimers of the FPV HA. These observations also indicate that, under certain conditions, the fusion peptide of the FPV HA can serve as a membrane anchor.